Organizational change and job performance the case of Landbank of the Philippines Iloilo lending center - De La Cruz, Dona Mae; Galuego, Mateo L.; Inamarga, Christine (2005)
This study is conducted to determine how organizational change affects the job performance of the employees of Land Bank of the Philippines, Iloilo Lending Center. This study is descriptive in nature and the sampling design used is the simple random sampling, a total of thirty (30) respondents from the Land Bank of the Philippines, Iloilo lending Center composed the total number of research respondents. The lottery technique was used to for the identification of these thirty respondents. The data collected undergone the descriptive analysis through frequencies and percentages. The results showed that organizational change really affects the job performance of the employees. In addition, job performance of the employees. In addition, job performance also affects the implementation of the job performance through the levels of work task by the employees. The researchers recommend that managers should encourage participation among employees before implementing an organizational change. Also recommended is the proper training and open-communication with in the organization through education. And lastly, for the managers to facilitate the change because the researchers believe that the managers are the proper authorities that can implement changes for the benefit of the whole organization.
Undergraduate Research (Mgt 199-Management Research). -- Iloilo City : UPV-CM, October 2005.